Screening of ligninase-producing bacteria from south east Pahang peat swamp forest soil - Mohamad Roslan, Muhamad Aidilfitri; Zainal Abidin, Zaima Azira; Mohd Omar, Suhaila (Malaysian Society for Microbiology, 2016)
Aims: Research on lignin degradation capability is previously restricted exclusively to fungal enzymes. However, recent studies had successfully revealed several soil bacterial strains that were able to produce ligninolytic enzymes. These bacterial ligninolytic enzymes were claimed to be more specific in catalysing cleavage of certain linkages between phenolic units of lignin polymers as compared to fungal enzymes. The present study focuses on screening for ligninase- producing bacteria isolated from South East Pahang Peat Swamp Forest (SEPPSF) soil using agar-based assay. Methodology and results: Thirteen isolates used in this study, which were selected based on distinctive colony morphology from our previous isolation work, showed decolourisation zone on Azure B plates screening. The ratio of decolourisation zones were measured to the ratio of the colony size and the biggest ratio was 2.22 by isolate AR1. Only 4 out of the 13 isolates were able to grow on lignin plates. Subsequently, the 4 isolates, AR3, AR8, AR10 and AR13 were tested on M1 agar supplemented with 3 ligninolytic enzyme indicator compounds which were tannic acid (TA), guaiacol and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) respectively. All four isolates showed growth on TA plates while only AR10 showed a clear brown coloration. An Intense reddish-brown colour formation was observed around the colony of isolates AR3 and AR10 on guaiacol plates while none exhibited green coloration around the colonies when tested on ABTS plates. Conclusions, significance and impacts of study: Isolate AR10 that was identified as Serratia sp. was perceived to be a potential ligninase-producer, though in-depth analysis has to be conducted in the future to determine the specific ligninolytic enzyme activities and characteristics. The application of different substrates is essential to investigate the ligninolytic potential and reaction of those bacterial enzymes towards different indicator compounds. This study is a preliminary endeavour concerning potential ligninolytic enzymes from bacteria as biocatalysts in various industrial processes. This is the first report on preliminary study for ligninolytic activities of soil bacteria from SEPPSF soil. Keywords: ligninolytic enzymes, bacteria, peat swamp forest, tannic acid, guaiacol